“LET’S MOVE!” CAMPAIGN: EDUCATION AND STIMULATION OF PHYSICAL EXERCISE IN OLDER ADULTS - Sundari Indah Wiyasihati; Hayuris Kinandita Setiawan; Purwo Sri Rejeki; Irfiansyah Irwadi (Jurnal Layanan Masyarakat, 2023)
The increase in human life expectancy has led to an increase in the number of older adults worldwide, including in Indonesia. The aging population raises sarcopenia as a further problem in geriatric medicine. Sarcopenia is a syndrome characterized by progressive skeletal muscle mass and strength loss. This syndrome is associated with reduced quality of life, increased risk of falls, and even death. Physical exercise is the only effective intervention strategy. Therefore, we designed this community service program for socializing the healthy lifestyle of the elderly with one focus on physical exercise as a promotive, preventive, and curative effort on the incidence of sarcopenia in the elderly. The method chosen was socialization and educating fifty-two pre-elderly and elderly target partners regarding the healthy lifestyle for the older adults and elderly exercise activities as stimulation. The "Let's Move!" campaign that has been implemented can socialize and increase the knowledge of target partners regarding sarcopenia and physical exercise as an intervention for prevention and treatment. The formulation of the main guidelines for safe exercise for the elderly can be useful for target partners who generally already have one type of condition that limits their ability to carry out activities of daily living.